2000
DOI: 10.1016/s0002-9440(10)64550-6
|View full text |Cite
|
Sign up to set email alerts
|

TPM3-ALK and TPM4-ALK Oncogenes in Inflammatory Myofibroblastic Tumors

Abstract: Inflammatory myofibroblastic tumors (IMTs) are neoplastic mesenchymal proliferations featuring an inflammatory infiltrate composed primarily of lymphocytes and plasma cells. The myofibroblastic cells in some IMTs contain chromosomal rearrangements involving the ALK receptor tyrosine-kinase locus region (chromosome band 2p23). ALK-which is normally restricted in its expression to neural tissues-is expressed strikingly in the IMT cells with 2p23 rearrangements. We now report a recurrent oncogenic mechanism, in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
431
2
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(459 citation statements)
references
References 34 publications
17
431
2
9
Order By: Relevance
“…A single case of IMT has been reported with a translocation involving 12q15 and an intragenic rearrangement of high mobility group I-C (36). Concurrently with the present report, tropomyosin (TPM)-ALK fusions involving TPM3-ALK and TPM4-ALK oncogenes were reported in two abdominal and one pulmonary IMT (37). In this series, 64% of IMT displayed ALK immunoreactivity but only 27% had ALK fusions by RT-PCR screening for TPM3-ALK and TPM4-ALK.…”
Section: Imt Is Classified With Intermediate Neoplasms In the Currentsupporting
confidence: 86%
See 1 more Smart Citation
“…A single case of IMT has been reported with a translocation involving 12q15 and an intragenic rearrangement of high mobility group I-C (36). Concurrently with the present report, tropomyosin (TPM)-ALK fusions involving TPM3-ALK and TPM4-ALK oncogenes were reported in two abdominal and one pulmonary IMT (37). In this series, 64% of IMT displayed ALK immunoreactivity but only 27% had ALK fusions by RT-PCR screening for TPM3-ALK and TPM4-ALK.…”
Section: Imt Is Classified With Intermediate Neoplasms In the Currentsupporting
confidence: 86%
“…Perhaps there is a family of neoplasms, the ALK family, of which ALCL (ALK lymphoma) and IMT with ALK abnormalities are the first recognized members. The recent finding of ALK tyrosine kinase gene expression in neuroblastoma (41) and the identification of specific TPM3-ALK and TPM4-ALK oncogenes in IMT (37) further support this hypothesis. The recognition of specific gene fusion partners of ALK rearrangements in IMT is incomplete, although a recent study has suggested TPM involvement.…”
Section: Imt Is Classified With Intermediate Neoplasms In the Currentmentioning
confidence: 72%
“…11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin. [19][20][21][22] To the best of our knowledge, this is the first report of a recurrent ALK locus rearrangement in a primary kidney tumor.…”
Section: Discussionmentioning
confidence: 99%
“…11 Subsequently, ALK rearrangements were found in several phenotypically different hematologic neoplasms [12][13][14] and in histogenetically unrelated inflammatory myofibroblastic tumor. [15][16][17][18] Recently, ALK rearrangements and EML4-ALK and KIF5B-ALK fusions were discovered in a subset of non-small cell lung carcinomas; 19,20 proteomics reports suggested a possible TPM4-ALK fusion in esophageal carcinoma; 21,22 and an exon array profiling study demonstrated the EML4-ALK fusion in 2.5% of breast and colon cancers. 23 ALK is also activated in B5 to 35% of neuroblastomas and neuroblastoma cell lines by a different mechanism involving point mutations and/or gene locus amplifications.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] It is composed of fibroblasts and myofibroblasts accompanied by an inflammatory infiltrate of plasma cells with variable lymphocytes and eosinophils (see Figure 1). 6 A reported 15-30% of patients have a clinical and laboratory syndrome of fever, malaise, weight loss, anemia, elevated erythrocyte sedimentation rate, thrombocytosis, polyclonal hypergammaglobulinemia, and other inflammatory marker elevations.…”
mentioning
confidence: 99%